Bibliometric analysis of scientific publications on "sustainable development goals" with emphasis on "good health and well-being" goal (2015-2019) - Waleed M. Sweileh (BMC, 2020)
Abstract Background Global progress in the United Nations' Sustainable Development Goals (SDGs) requires significant national and international research efforts and collaboration. The current study aimed to provide policymakers, academics, and researchers with a snapshot of global SDGs-related research activity. Method This was a cross-sectional descriptive bibliometric study. SciVerse Scopus was used to retrieve SDGs-related research publications for the period from 2015 to 2019. Results In total, 18,696 documents were found. The Sustainability journal ranked first (n = 1008; 5.4%) in the number of SDGs-related publications. The World Health Organization was the most active institution in publishing SDGs-related documents (n = 581; 1.3%). Most of the retrieved documents belonged to SDG 17 (partnership) followed by SDG 13 (climate action), and SDG 12 (responsible consumption and production), while SDG 7 (affordable and clean energy) had the least number of publications. The European region (n = 9756; 52.2%) had the highest research contribution while the Eastern Mediterranean region (n = 1052; 5.6%) had the least contribution. After exclusion of SDG 17, the SDG 3 (good health and well-being) was the top researched SDG for the African region, the Eastern Mediterranean regions, and the South-Eastern Asian region. For the region of the Americas, European region, and the Western Pacific region, the SDG 13 (climate action) was the most researched. The SDG 7 (affordable and clean energy) was the least researched in the African region, the region of the Americas, the European region, and the South-East Asian region. In the Eastern Mediterranean region, SDG 10 (reduced inequality) was the least researched while in the Western Pacific region, SDG 5 (gender inequality) was the least researched. The most researched targets of SDG 3 were targets 7 (sexual and reproductive health services) and 8 (universal health coverage) while the least researched targets were 5 (substance use disorders) and 9 (death from hazardous materials). International research collaboration within SDG 3 between high- and low-income countries was inadequate. Conclusion The analysis presented in the current study are useful for researchers, institutes, governments, funding agencies, and policy-makers. Countries in Africa, the Middle East, and South-East Asia need to increase their funding and research collaboration in the field of SDGs.